2003
DOI: 10.1107/s0108767303006251
|View full text |Cite
|
Sign up to set email alerts
|

Relations between the zinc-blende and the NaCl structure type

Abstract: A new model for the transformation from the zinc-blende to the NaCl type is developed on the basis of the deformation of a 4-connected heterogeneous sphere packing in space group P3(2). The geometrical features of this transition are discussed by investigating the analogous deformations of a 4-connected homogeneous sphere packing in the supergroup P3(2)21 of P3(2). In this space group, the atomic arrangement corresponds to a diamond configuration. During the phase transition, it is deformed under preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
0
25
0
4
Order By: Relevance
“…In another study of the transition mechanism, using sphere packing methods and no energy considerations, Sowa also obtained the Imm2 subgroup mechanism 20 and more recently proposed an additional mechanism with P3 2 symmetry. 21 Catti 16 and Sowa 20,21 have noted that in the Imm2 and P 3 2 TPs no silicon-carbon bonds are broken. However, no further study is reported on the comparison of the two TPs.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of the transition mechanism, using sphere packing methods and no energy considerations, Sowa also obtained the Imm2 subgroup mechanism 20 and more recently proposed an additional mechanism with P3 2 symmetry. 21 Catti 16 and Sowa 20,21 have noted that in the Imm2 and P 3 2 TPs no silicon-carbon bonds are broken. However, no further study is reported on the comparison of the two TPs.…”
Section: Introductionmentioning
confidence: 99%
“…Limpijumnong, Lambrecht, 2001;Sowa, 2001Sowa, , 2005aShimojo et al, 2004) and between zincblende-and NaCl-type structures (e.g. Sowa, 2000bSowa, , 2003Shimojo et al, 2000;Catti, 2001;Hatch et al, 2005). Experimentally determined relations between the orientations of the structures before and after a phase transition may support or disprove possible transition models.…”
Section: Discussionmentioning
confidence: 93%
“…The occurrence of sphere-packings with cubic inherent symmetry within trigonal lattice complexes (cf. Sowa, Koch and Fischer, 2003;Sowa andKoch, 2004, 2005) were used for checking the Table. Altogether, 10 invariant and 8 univariant cubic lattice complexes occur as limiting complexes within the trigonal crystal system. All lattice complexes of types (ii) and (iiia) (cf.…”
Section: Derivation and Resultsmentioning
confidence: 99%
“…Consequently, a possible transition path may be described with the aid of a lattice complex having as well Fd 3 3m 8a (cubic diamond configurations, D) as Pm 3 3m 1a (cubic primitive lattices, P) as limiting complexes. Sowa (2003) showed that P3 2 21 6c is one of the lattice complexes with this property. As listed in Table 1, Pm 3 3m 1a occurs two times as limiting complex, namely at 1 = 3 1 = 3 1 = 4 and at 2 = 3 2 = 3 1 = 4 .…”
Section: Applicationsmentioning
confidence: 90%
See 1 more Smart Citation